2023
DOI: 10.3389/fsufs.2023.1271921
|View full text |Cite
|
Sign up to set email alerts
|

High-capacity boronate affinity-based template-immobilized surface imprinted silica nanoparticles for rapid, selective, and efficient extraction and determination of lincomycin in milk and chicken

Yansong Zhang,
Yihan Ding,
Yidan Ma
et al.

Abstract: BackgroundLincomycin, a natural antibiotic, is widely used by animal and fishery husbandries to prevent infections and treat diseases. It endangers people’s health when they eat foods containing lincomycin residue, especially the frequent consumption of milk and chicken products containing lincomycin. Hence, it is extremely important to evaluate the content of lincomycin in food samples. However, a direct analysis of lincomycin in milk and chicken is quite difficult because of its very low concentration level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Clearly, such equilibrium time of SiO 2 @FFPBA@MIPs for SA was lower than that of other imprinted polymers (8–90 min). 15,28–31 This result indicated that SiO 2 @FFPBA@MIPs for SA showed good binding kinetics.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Clearly, such equilibrium time of SiO 2 @FFPBA@MIPs for SA was lower than that of other imprinted polymers (8–90 min). 15,28–31 This result indicated that SiO 2 @FFPBA@MIPs for SA showed good binding kinetics.…”
Section: Resultsmentioning
confidence: 84%
“…The p K a value of FFPBA was reported to be approximately 5.8 due to the presence of electron-withdrawing groups in FFPBA. 28 Clearly, this kind of boronic acid ligand could work under low pH conditions of 6.0 (see Fig. 6).…”
Section: Resultsmentioning
confidence: 97%
“…The p K a value of FFPBA was reported to be approximately 5.8 due to the presence of electron-withdrawing groups in FFPBA. 36 Clearly, this kind of boronic acid ligands could work under low pH conditions of 6.0 (see Fig. 8).…”
Section: Resultsmentioning
confidence: 96%
“…Silica nanoparticles (SiO 2 ), due to their good biocompatibility, low toxicity, easy post modification, high yield synthesis and easy preparation, can be well used as solid substrates. 33–36 Thus, high-density FFPBA ligands can be formed on the surface of SiO 2 by post-modification reactions. Additionally, the imprinting coating plays a crucial role in determining the binding characteristics of imprinted materials.…”
Section: Introductionmentioning
confidence: 99%
“…The structures of the boronic acid ligands and supporting materials determine the binding affinity [ 21 ]. Due to the presence of electron-withdrawing groups, the FFPBA used exhibited a low p K a value of 5.8 [ 49 ]. The boronic acid ligand was able to work at a relatively low pH condition of 6.0 ( Figure 8 ).…”
Section: Resultsmentioning
confidence: 99%